Shielding Parenteral Nutrition From Light Improves Survival Rate in Premature Infants: A Meta‐Analysis. (16th September 2015) - Chessex, Philippe; Laborie, Sophie; Nasef, Nehad; Masse, Benoit; Lavoie, Jean‐Claude
Abstract : Background: Intravenous nutrition preparations that are not photoprotected generate oxidants, which are deleterious for cell survival. The question remains: are these observations of clinical relevance in individuals receiving parenteral nutrition (PN), especially in those who exhibit immature antioxidant defenses such as premature infants? Objective: To review clinical trials reporting the effect of light‐exposed vs light‐protected PN to determine whether photoprotection reduces neonatal mortality in preterm infants. Data source: Electronic databases, abstracts in relevant journals, and references in manuscripts between 1980 and 2014. Selection criteria: Newborn, premature infants, PN, photoprotection, shielding from light, randomization, mortality, death. Methods: Consensus for inclusion reached by 2 reviewers; meta‐analysis of trials and observational studies reporting mortality at 36 weeks' gestational age or hospital discharge. Results: Four trials meeting selection criteria, which involved a total of 800 newborn premature infants, were included. Across trials, gestational age (mean ± SD) ranged from 26 ± 1 to 31 ± 2 weeks, birth weight from 775 ± 161 to 1588 ± 366 g, and mortality from 5%–32%. Mortality in the light‐protected group was half of that in the light‐exposed group (95% confidence interval, 0.32–0.87) and twice as high in males compared with females (χ 2, P = .01). Conclusion: Shielding PN from light has vital repercussions that call for action to provide photoprotected delivery systems and infusion sets in premature infants. Further studies should be extended to the increasing number of children and adults receiving long‐term home PN to evaluate the effects of light protection on severe complications that impede their quality of life.